(untitled) (Revista Cientifica Ingenio Magno, 2020)
This project creates a computational bridge assessment tool taking decision criteria and many more variables that engage in decision-making for immediate intervention, using more defined criteria of damage structural, hydraulic and geotechnical, bridge weighted risk indicators and consequence indicators, the criteria of transit level and strategic value of the bridge were used, with the respective subcriteria as functional elements, infrastructure and superstructure, undermining of the bridge in piles, stirrups and fins, degree of importance within the road network, daily average transit - TPDS, importance of the track, impact by closure, difficulty of recovery of the track, slope of the section, date bridge construction, bridge structural configuration, alternating tracks and environmental sensitivity; covering the vast majority of the technical-political and socio-environmental criteria that intercede in decision-making for an intervention in the evaluation of bridges Using Saaty’s decision-making process model (1), although the methodology allows to generate weight values, through experts or the judgment of values of a decisor; in this project, weights were generated qualitatively by measuring their consistency, which were taken on the basis of the three bridge assessments carried out by INVIAS in 1996-1997, 2001-2002 and 2008-2009(16), these weights could be modified by the administrator, program expert in case criteria or "subjective judgments made by experts" (2) are required, a peer-to-peer comparison matrix of factors is made on a rating scale according to preferences, using the scale of Saaty values (3) of equal or extreme importance i.e. 1 (one) when the comparison is weak and up to 10 (ten) when the comparison is strong; the process of normalizing the matrix is carried out to obtain the relative weights for each criterion, performing the calculation of the congruence relationship in order to verify the consistency of the individual judgments, obtaining the vector of priority for each pair of criteria and in the ordering of priorities for decision-making in bridge management intervention.